River Water Quality Spatial Analysis Based On Physical Parameter Throughout Krueng Daroy In Banda Aceh - Mulyani .; Marwan .; Nazli Ismail (Journal of Aceh Physics Society, 2012)
Water quality research has been done along Krueng Daroy in Banda Aceh. The research is aimed to observe water quality based on physical parameters and to identify the sources of pollutant spatially. We measured temperature, turbidity, color, pH, odor, TDS and electrical conductivity, where the data were collected using thermometer, turbidity meter, spectrophotometer, pH meter, TDS meter and conductivity meter, respectively. The physical parameters of water in the upstream area fulfilled the standard of the Health Minister of Republic Indonesia according to law Number 907/ MENKES/ SK/VII/2002 and it is suitable for household needs. However, the water at the downstream area are mostly polluted